Semi-Automatic 2D-to-3D Conversion Using Low-Rank Matrix Recovery - Yuan, Hongxing (International Journal of Online and Biomedical Engineering (iJOE), 2018)
Semi-automatic 2D-to-3D conversion is a promising solution to 3D stereoscopic content creation. However, the depth continuous transition between user marked neighboring regions will be lost when user scribbles are sparse. To help solve this problem, a piecewise-continuity regularized low-rank matrix recovery method is developed. Our approach is based on the fact that a depth-map can be decomposed into a low-rank matrix and an outlier term matrix. First, an initial dense depth-map is interpolated from the user scribbles using matting Laplacian scheme under the assumption that depth-map is piecewise-continuous. Second, a piecewise-continuity constrained low-rank recovery model is developed to remove outliers which are introduced by the interpolation. Experimental comparisons with existing algorithms show that our method demonstrates significant advantage over depth continuous transition between neighboring regions.